Apakah Pembiayaan Mudharabah dan Pembiayaan Musyarakah Memiliki Dampak yang Berbeda Terhadap Risiko Kredit Bank Umum Syariah? - Alifka Farisa Putri; Yulfan Arif Nurohman (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to analyze the differences in the impact of Mudharabah financing and Musyarakah financing on credit risk. Specifically, this study wants to test whether Mudharabah financing tends to be riskier than Musyarakah financing. In this study, data were collected using purposive sampling techniques with specific criteria. With this method, the author was able to identify 9 banking sectors that met the criteria and produced a total of 108 research data used as the basis for analysis. Data analysis was carried out using classical assumption tests, multiple linear regression, partial tests, simultaneous tests, and determination tests assisted by SPSS. The results of the partial test (T) showed that Mudharabah financing had no significant effect on NPF, while Musyarakah financing was proven to have a significant effect on NPF. Based on these findings, it can be concluded that Mudharabah financing is not riskier than Musyarakah financing. The determination test produced a value of 0.686 or 68.6%, which indicates that Mudharabah and Musyarakah financing together have an effect on NPF, while the remainder 31.4% is influenced by other factors outside this research model. The understanding of Mudharabah and Musyarakah financing is crucial in managing the performance of Islamic banks concerning Non-Performing Financing (NPF) risk. The research findings support the agency theory in the context of Islamic financing, highlighting the importance of risk management and the relationship between fund owners and fund managers.